Principles of Labor Law - Della Puspitasari; Dian Yudhantara Syahputra; Ertina Dewi Setyaningrum; Muhammad Dinar Bagoes Oetomo; Tegar Prasetyo Utomo; Ovan Dwi Miftakhus Shurur (Proceeding International Conference Restructuring and Transforming Law, 2022)
In an effort to understand labor law, it is necessary to understand the limitations of understanding labor law. There is an understanding that focuses on certain aspects without paying attention to other aspects. The definition of labor law must also pay attention to the scope of conduct according to time and region.As for the deployment and utilization of manpower, which is the subject of discussion in the field of labor law, which specifically discusses labor issues broadly. The workforce includes everyone who is or will be doing work. Broadly speaking, the deployment and utilization of manpower aims to realize the mandate contained in the Constitution of the Republic of Indonesia article 27 paragraph 2 that every worker has the right to work and income that is decent for humanity. For this reason, the state through the government formulates a strategy in the form of policies and work programs in the context of manpower planning at the macro and micro levels whose operational objectives are labor development. Manpower development is carried out through the utilization of every workforce in order to become a potential supporter of development. The principles in manpower development include the principle of integration between the center and the regions, between the macro and micro levels as well as between sectors. The next principle is equal opportunity to get a job, as well as the principle of non-discrimination in the implementation of work/position.Whereas in Indonesia, industrial relations involve actors in the process of producing goods and/or services consisting of elements of entrepreneurs, workers/laborers, and the government based on the values of Pancasila and the 1945 Constitution of the Republic of Indonesia. Industrial relations prioritizes the functions of the parties. in industrial relations in order to achieve the ideals of the state. In principle, the goal to be achieved in industrial relations is to get to work for workers and business activities for entrepreneurs.